Clinical characteristics and treatment outcomes of 68 patients with spontaneous iliac vein rupture: A case report and systematic review - Li Zhui; Feng Yangyang; Wei Miao; Cui Hong; Zeng Qiu; Huang Wen; Ren Wei; Zhao Yu (Heliyon, 2023)
Objective: Spontaneous iliac vein rupture (SIVR) is a rare but life-threatening condition with limited understanding regarding its clinical presentation, pathogenesis, diagnosis, management, and risk factors for mortality. This study aims to address this gap by providing comprehensive insights into SIVR through personal case reports and a systematic review of previous cases. Methods: We detail a case of right SIVR caused by inappropriate positioning of the stent in the inferior vena cava and systematically reviewed previous cases. Logistic regression analysis was used to identify risk factors for mortality. Results: Our SIVR case was successfully managed with percutaneous mechanical thrombectomy and covered stent placement. In the systematic review, 68 patients were included in the analysis with an average age of 62.01 ± 13.25 years; 86.76% were female, 91.17% had left iliac vein rupture, 55.88% presented hemodynamic instability, 76.47% had lower abdomen or iliac fossa pain, 67.64% had deep venous thrombosis (DVT), and 32.35% had May‒Thurner syndrome (MTS). The mortality rates of conservative treatment and open surgery were 2.94% and 17.65%, respectively. All 12 patients receiving endovascular treatment survived. The factors associated with a worse outcome were younger age (52.86 ± 12.96 years, OR: 1.085, 95% CI: 1.002–1.174) and SIVR patients without DVT (OR:10.111, 95% CI: 1.637–62.443). Conclusion: This first systematic review on SIVR shows that SIVR should be highly suspected in elderly females who develop lower extremity DVT and concurrent lower abdominal pain, particularly those with a retroperitoneal mass and unstable hemodynamics. Thrombosis secondary to MTS may be the main cause of SIVR. Angiography and endovascular therapy should be prioritized for DVT patients with unexplained retroperitoneal hematoma. This study classifies SIVR into two types: iliac vein rupture alone and iliac vein rupture with DVT. These findings provide critical insights for clinicians to accurately diagnose and manage SIVR, thereby improving patient outcomes.